Development of magic indonesia jarimatic method in counting to improve learning outcomes of numbers in elementary school - Sriyatun, Sriyatun; Saputro, Bagus Ardi; Sumarno, Sumarno (Jurnal Konseling dan Pendidikan, 2025)
This research develops a counting method, namely the Indonesian magic jarimatik method, which is motivated by students' numeracy skills that are not in accordance with national standards in the AKM, limited counting methods as a source of learning numbers used in elementary schools in the teaching and learning process. This study aims to determine the effectiveness of the JMI method in learning Mathematics to improve elementary school learning outcomes. This research uses the ADDIE development research model, namely: Analysis which is related to the activity of analyzing the work situation and the environment so that it can be found what products need to be developed, Design is an activity of designing products according to needs, Development is an activity of making and testing products, Implementation is an activity of using products, Evaluation is an activity of assessing whether each step of activities and products that have been made are in accordance with specifications or not.   Through these results it can be concluded that the use of the JMI method in learning Mathematics is declared effective because it can have an influence on improving the learning outcomes of elementary school students' numbers.